2007
DOI: 10.1038/sj.cr.7310125
|View full text |Cite
|
Sign up to set email alerts
|

Nanog and transcriptional networks in embryonic stem cell pluripotency

Abstract: Several extrinsic signals such as LIF, BMP and Wnt can support the self-renewal and pluripotency of embryonic stem (ES) cells through regulating the "pluripotent genes." A unique homeobox transcription factor, Nanog, is one of the key downstream effectors of these signals. Elevated level of Nanog can maintain the mouse ES cell self-renewal independent of LIF and enable human ES cell growth without feeder cells. In addition to the external signal pathways, intrinsic transcription factors such as FoxD3, P53 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
391
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 532 publications
(415 citation statements)
references
References 44 publications
(69 reference statements)
16
391
1
7
Order By: Relevance
“…It indicated that porcine Nanog had similar properties in PFF, at least partially, which were described for Nanog in primate and mouse ESCs. In both humans and mice, research shows that Nanog could bind to the upstream element of Oct4 and cooperate with other core transcription factors to activate Oct4 expression thereby maintaining the pluripotency (Boyer et al, 2005;Rodda et al, 2005;Pan and Thomson, 2007). In mESCs, Nanog interacts with Sall4 in a way similar with that of Oct4 and Sox2 to activate each other, thus helps to set up the pluripotency regulatory circuits .…”
Section: Discussion Transient Elevation Of Nanog Expression Can Activmentioning
confidence: 99%
See 1 more Smart Citation
“…It indicated that porcine Nanog had similar properties in PFF, at least partially, which were described for Nanog in primate and mouse ESCs. In both humans and mice, research shows that Nanog could bind to the upstream element of Oct4 and cooperate with other core transcription factors to activate Oct4 expression thereby maintaining the pluripotency (Boyer et al, 2005;Rodda et al, 2005;Pan and Thomson, 2007). In mESCs, Nanog interacts with Sall4 in a way similar with that of Oct4 and Sox2 to activate each other, thus helps to set up the pluripotency regulatory circuits .…”
Section: Discussion Transient Elevation Of Nanog Expression Can Activmentioning
confidence: 99%
“…We speculate that transient high Nanog expression can activate part of the pluripotency related genes in PFF, but it is not enough for inducing PFF to a fully pluripotent state, thus cannot set up the stable regulatory circuit. Pan et al also indicate that the key pluripotent factors always work together to control the whole set of pluripotency machinery rather than work individually (Pan and Thomson, 2007). So in a partially transformed PFF, these activated pluripotent genes can be easily silenced in many ways including DNA highly methylating.…”
Section: Pluripotent Genes Expression Cannot Be Maintained During G41mentioning
confidence: 99%
“…Two characteristic properties of hESCs, pluripotency, a capacity to differentiate into all fetal and adult cell lineages, and the ability to undergo symmetrical self-renewing divisions, are largely controlled at the transcriptional level (reviewed in Chen and Daley, 2008). In undifferentiated hESCs, pluripotency genes such as OCT4 (also called POU5F1 ), NANOG and SOX2 are expressed, whereas genes involved in differentiation are transcriptionally inactive (reviewed in Sun et al, 2006; Pan and Thomson, 2007). Decreased expression of pluripotency genes induces differentiation (Niwa et al, 2000), and thus proper transcriptional regulation is essential for self-renewal of undifferentiated hESCs.…”
Section: Introductionmentioning
confidence: 99%
“…Undifferentiated human cells express at high level the pluripotency markers OCT4, SOX2 and NANOG, the cell surface markers stage-specific antigen-4 (SSEA4) and TRA-1-60; and alkaline phosphatase [169][170][171]. The levels of expression of these markers decline rapidly once differentiation has begun.…”
Section: Markers For Differentiation Into Cardiomyocyte Lineagementioning
confidence: 99%